Age-Related Changes in Normal-Appearing Brain Tissue and White Matter Hyperintensities: More of the Same or Something Else? - Spilt, Aart; Geeraedts, Tychon; de Craen, Anton J. M.; Westendorp, Rudi G. J.; Blauw, Gerard J.; van Buchem, Mark A. (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Cerebral white matter (WM) hyperintensities are a frequent finding in elderly people, and lowering of cerebral magnetization transfer ratio (MTR) has been observed. The aim of this study was to assess the relationship between age-related WM hyperintensities and MTR changes in the brain.METHODS: We performed MR imaging in a group of young subjects, a group of elderly individuals with minimal WM hyperintensities, and a group of elderly individuals with abundant WM hyperintensities. In addition, we performed volumetric MTR analysis of the whole brain and of the normal-appearing WM (NAWM) in these groups.RESULTS: Volumetric MTR parameters differed between elderly and young patients. Mean MTR ± standard error of the mean (SEM) was 34.0% ± 0.12% in the young, 33.0% ± 0.08% in the elderly with minimal WM hyperintensities, 32.8% ± 0.09%) in the group with abundant WM hyperintensities. Peak height (number of voxels ± SEM) was 122 ± 1.2 in the young, 99 ± 1.5 in the elderly with minimal WM hyperintensities, and 98 ± 1.6 in the group with abundant WM hyperintensities. Mean MTR of NAWM was lower in the elderly compared with the young (36.7% ± 0.12%) but did not differ between subjects with minimal (36.0% ± 0.11%) and those with abundant WM hyperintensities (35.9% ± 0.13%).CONCLUSION: Our results show that aging gives rise to changes in normal-appearing brain tissue. These changes, which can be detected on magnetization transfer imaging, seem to have no relationship with age-related WM hyperintensities and might have a different etiology.